Comparing the adequacy of the MNA-SF, NRS-2002 and MUST nutritional tools in assessing malnutrition in hip fracture operated elderly patients. Issue 5 (October 2016) - Koren-Hakim, Tamar; Weiss, Avraham; Hershkovitz, Avital; Otzrateni, Irena; Anbar, Ronit; Gross Nevo, Revital Feige; Schlesinger, Agata; Frishman, Sigal; Salai, Moshe; Beloosesky, Yichayaou
Summary: Background & aims: Malnutrition is common in hip fracture elderly patients. There is no gold standard for screening nutritional risk. We compared the adequacy of 3 screening tools, their association to nutritional measurements and their ability to predict outcome. Methods: The Mini Nutrition Assessment Short Form (MNA-SF), the Malnutrition Universal Screening Tool (MUST) and the Nutrition Risk Screening 2002 (NRS-2002) were prospectively determined. Length of stay (LOS), complications, 6 months readmission and up-to 36 months mortality were recorded. Results: 215 operated patients were included: 154 (71.6%) were women; mean age was 83.5 ± 6.09 years (66–104). According to the MNA-SF, 95 patients were well-nourished, 95 were at risk of malnutrition and 25 were malnourished. Based on the MUST, 171 patients were at a low risk of malnutrition, 31 at a medium risk, 13 at a high risk. According to the NRS-2002, 134 patients were at a low risk of malnutrition, 70 at a medium risk, 11 at a high risk. A significant relationship between the nutritional groups of the 3 scores (p < 0.001) was found. In all screening tools, body mass index, weight loss and food intake prior to admission were found to be related to the patients' nutritional status (p < 0.001). No differences in LOS and complications were found between the patients' nutritional status of each screening tool; only the MNA-SF predicted that well-nourished patients would have less readmissions during a 6 month follow-up (p = 0.024). During a 36 month follow-up, 79 patients died. According to the MNA-SF, mortality was lower in the well-nourished patients vs. the malnourished (p = 0.001) and at risk of malnutrition patients (p = 0.01). A less significant association was found between the NRS-2002 patients' nutritional status and mortality (p = 0.048). The MUST did not reveal this relationship. Conclusions: All screening tools were adequate in assessing malnutrition parameters in hip fracture operated elderly patients, however, only the MNA-SF could also predict readmissions and mortality. Highlights: Malnutrition rate is high in hip fracture elderly patients. The MNA-SF correlates the most with malnutrition clinical parameters. The MNA-SF can predict lower readmissions in well-nourished patients. The MNA-SF can indicate lower long-term mortality in the well-nourished patients.